Peranan Diplomat Indonesia dalam Memperjuangkan Palestina di PBB (Masa Presidency of the UNSC Mei 2019) - Rezasyah, Teuku (Jurnal ICMES, 2019)
In May 2019, Indonesia served as President of the UN Security Council. During her presidency, Indonesia sought to achieve world peace by raising the theme "Investing in Peace." This research seeks to explain the role of Indonesian diplomats in defending Palestine during the presidency especially in the issue of Israeli illegal settlements in the West Bank. The research was conducted qualitatively by examining official documents and mass media, as well as conducting interviews with primary informant. The concept used in this research is national role conception from Holsti. This research finds that Indonesian diplomats carry out their role in fighting for Palestine driven by the national role conception as the bastion of revolution liberator or as a nation that wants to abolish colonialism in another country, namely Palestine.